Influence of nanodiamond incorporation on the impact strength of repaired denture base acrylic resin: an in vitro study - Abdel-Nasser M. Emam (Amaltea Medical Publishing House, 2024)
Aim. This research aims to evaluate the effects of integrating Nanodiamond on the impact strength of repaired denture base resin. Methodology. Sixty acrylic resin specimens, sized 50×6×4 mm³ with a v-notch, were created from heat-polymerized acrylic resin. Ten specimens were kept intact while the other 50 specimens were sectioned to half and prepared with 45° beveling and a 2.5mm-repair gap. Nanodiamond particles were added to autopolymerized repair resin and repaired specimens were placed in five categories (n=10) according to Nanodiamond concentrations, unmodified as a control, 0.25%, 0.5%, 0.75%, and 1% ND by weight. Each specimen half was repositioned in a metal jig, and the repair resin was applied to the repair area. Subsequently, all specimens underwent finishing, polishing, and immersion in distilled water before Charpy's impact testing. Data analysis employed Tukey's post hoc test (with significance α=0.05) and one-way ANOVA. Results. Results showed that in comparison with the control group, the impact strength of repaired denture base resin significantly increased with 0.25% and 0.5% Nanodiamond addition to repair resin (significance at P ˂0.001). While it insignificantly decreased with 0.75% and 1% Nanodiamond (P=0.108 and P=0.615) and 1% presented the lowest value of impact strength (3.48±0.43 KJ/m2). Conclusion. Adding a small amount of Nanodiamond to autopolymerized repair resin demonstrated an increase in the impact strength of repaired acrylic denture base resin. The highest impact strength was recorded with 0.25% ND (6.24±0.55 KJ/m2), followed by 0.5%ND (5.93±0.21 KJ/m2), whereas 1%ND exhibited the lowest impact strength value (3.48±0.43 KJ/m2).